Investigating carbon nanotube - polymer blends for organic solar cell applications - Stranks, S (2011)
This thesis describes studies on nanohybrid systems consisting of single-walled carbon nanotubes (SWNTs) with monolayer coatings of semiconducting polymers. Steady-state and time-resolved optical and high-resolution microscopy experiments were used to investigate the blends. These materials show promise for use in organic photovoltaics (OPVs) owing to the high carrier mobilities and large aspect ratios of SWNTs, the controllable solubilisation of tubes with various polymers and the broad light-harvesting abilities of organic polymers. Chapters 1 and 2 introduce the theory and background behind the work and present a literature review of previous work utilising carbon nanotubes in OPV devices, revealing poor performances to date. The experimental methods used during the thesis are detailed in Chapter 3 and the solution processing techniques used to prepare the polymer–nanotube blend samples are described in Chapter 4. Chapter 5 describes a study on a nanotube blend with a thiophene polymer, a system previously unsuccessfully implemented into OPV devices. Ultrafast spectroscopic measurements showed that electrons can transfer on a 400 fs time scale from the polymer to nanotubes and the conditions to allow long-lived free charges to be produced were found. The study is extended in Chapter 6 to show that nanostructures consisting of a nanotube coated in one polymer can then be coated by a second polymer and that these nano-engineered structures could be implemented into OPV devices. The use of a competition binding process to isolate purely semiconducting nanotubes dispersed with any desired polymer is then described in Chapter 7. Finally, Chapter 8 introduces systems consisting of chains of porphyrin units, nature’s light-harvesting systems, bound to nanotubes and the blends were found to exhibit the required electronic alignment for use in OPVs. The work described in this thesis provides an explanation for the poor device behaviour of nanotube–polymer blends to date and, in particular, demonstrates several nanohybrid systems that show particular promise for improved OPV applications.